Experiencing Troubles in Placing Modifiers in Students’ Teaching Practice Stories Across Disciplines - Naja, Fatmaainun; Hawa, Faiza; Yulianti, Fitri (Universitas Pahlawan Tuanku Tambusai, 2025)
Mastering grammar is essential for English learners, particularly the accurate placement of modifiers, which is often overlooked in academic writing. This research investigates the types of misplaced modifiers found in the teaching practice blog posts written by SEA Teacher participants. Misplaced modifiers can disrupt clarity and change the intended meaning of a sentence, yet they are often overlooked in academic writing instruction. Referring to Fowler and Aaron’s (2012) classification, this research aims to identify and analyze seven types of misplaced modifiers. Using a descriptive qualitative method, the researcher analyzed 30 narrative blog posts by SEA Teacher participants. The data were collected by identifying sentences that contained misplaced modifiers, then categorizing them based on their types. The analysis reveals that the most frequently occurring type is misplaced phrases and clauses (36.4%), followed by incorrect adverb placement (21.2%). These two types are dominant because they involve longer, more complex sentence structures where the intended meaning is often lost when modifiers are placed too far from the words they describe. Less frequent errors include squinting modifiers, limiting modifiers, and the incorrect order of adjectives. These findings indicate the need for more explicit grammar instruction to help pre-service teachers improve their syntactic accuracy in academic and reflective writing.